The Implementation of Agricultural-Based Industrialization Policy and Its Impact on Community Welfare in West Nusa Tenggara Province - Budiman, Arif; Fatmawati, Fatmawati; Mahsyar, Abdul; Hakim, Lukman (Universitas Muhammadiyah Gorontalo, 2025)
Industrialization has long been regarded as a key driver of economic transformation in developing countries, including Indonesia, where agriculture remains the backbone of many regional economies. In West Nusa Tenggara (NTB) Province, the challenge of enhancing community welfare requires innovative policy strategies, one of which is agricultural-based industrialization. This study aims to analyze the influence of the implementation of agricultural-based industrialization policy on community welfare in NTB Province. The research focuses on communication, resources, disposition, and bureaucratic structure as key determinants of policy implementation success. A quantitative approach was employed using a survey method involving 69 respondents. Data analysis included validity and reliability tests, classical assumption tests, multiple linear regression, as well as t-tests and F-tests. The results indicate that all four variables have a positive and significant effect on policy implementation. The coefficient of determination (R²) of 0.740 suggests that 74% of the variance in policy implementation can be explained by the independent variables. These findings imply that effective policy planning and execution, supported by clear communication, adequate resources, competent implementers, and a well-structured bureaucracy, significantly contribute to improving community welfare in the NTB region